Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1002/jcla.24269
|View full text |Cite
|
Sign up to set email alerts
|

Reference intervals for coagulation tests in adults with different ABO blood types

Abstract: Introduction: Coagulation tests are affected by many factors, such as age, race, and gestation. Although coagulation test results vary by ABO blood type, reference intervals of different ABO blood groups remain to be determined. This study aims to investigate the reference ranges of coagulation tests for different ABO blood groups in the Han population in South China. Methods: A retrospective study was conducted in the First Affiliated Hospital of Shantou University Medical College. In all, 9600 individuals ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 22 publications
(54 reference statements)
0
0
0
Order By: Relevance
“…However, the difference in APTT levels among the non-O blood types did not significantly differ. Chen et al have also found the same conclusion[ 40 ]. Although a relationship may be present between the ABO blood type and APTT, our study found that APTT did not affect the occurrence of PICC-VTE, which was similar to the results of Cardoso et al[ 41 ].…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…However, the difference in APTT levels among the non-O blood types did not significantly differ. Chen et al have also found the same conclusion[ 40 ]. Although a relationship may be present between the ABO blood type and APTT, our study found that APTT did not affect the occurrence of PICC-VTE, which was similar to the results of Cardoso et al[ 41 ].…”
Section: Discussionsupporting
confidence: 64%
“…Moreover, previous studies have demonstrated that patients with non-O blood types have a higher risk of pulmonary embolism(PE) and deep venous thrombosis (DVT) [ 37 , 38 ], whereas those with the O blood type have an increased risk of bleeding[ 28 ]. Another study found that the O blood type had a higher APTT level than the non-O blood type[ 39 ]. To explore the relationship between ABO blood type and APTT levels, we compared APTT levels among the different blood types of 8477 patients in this study.…”
Section: Discussionmentioning
confidence: 99%